RAPID QUANTIFICATION OF HUMIC AND FULVIC ACIDS BY HPLC IN NATURAL WATERS - Wu F.C.; Evans R.D.; Dillon P.J.; Cai Y.R. (My University, 2007)
A simple method based on high-performance size-exclusion chromatography (HPSEC) has been developed for rapid quantification of humic and fulvic acids (HA and FA) in stream waters. A Tsk-gel column was used to separate natural dissolved organic matter (DOM) into two components: peak A and B. In terms of HPSEC chromatograms and fluorescence patterns, peak A and B were similar to the corresponding XAD-extracted HA and FA, respectively. It is suggested that peak A fraction mainly consisted of HA, and peak B fraction FA. The similar separation of HA and FA using HPSEC and a conventional XAD method suggests the consistency of molecular size distribution and physical-chemical properties of DOM. HPSEC offers a simple and rapid method for the quantification of HA and FA instead of tedious extractions of humic substances. Analyses of natural water samples show that the calculation of HA/FA based on UV absorbance was under- or over-estimated, the calibration using the extracted HS allows a more accurate quantification. The fast screening of HA and FA provides useful quantitative and qualitative information that can be used in environmental or monitoring studies. © 2007 Elsevier Ltd. All rights reserved.